2016
DOI: 10.1002/jmri.25178
|View full text |Cite
|
Sign up to set email alerts
|

MR neurographic orthopantomogram: Ultrashort echo‐time imaging of mandibular bone and teeth complemented with high‐resolution morphological and functional MR neurography

Abstract: The proposed technique of MR neurographic orthopantomogram exploiting UTE imaging complemented with high-resolution morphological and functional MR neurography was feasible and allowed comprehensive assessment of osseous texture and neural microarchitecture in a single examination. J. Magn. Reson. Imaging 2016;44:393-400.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 26 publications
1
27
0
1
Order By: Relevance
“…Our study showed that FA values of the IANs ranged from 0.37 to 0.49, which were similar to the results in their study. 18 Our study also showed that the 95% CIs of intrasubject variabilities in ADC and FA were within a narrow range. According to several previous studies Dentomaxillofac Radiol, 45, 20160200 birpublications.org/dmfr DTI of the IAN using 3T MRI that evaluated DTI of the peripheral nerves, the FA of an injured nerve became significantly lower than that of the normal nerve.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Our study showed that FA values of the IANs ranged from 0.37 to 0.49, which were similar to the results in their study. 18 Our study also showed that the 95% CIs of intrasubject variabilities in ADC and FA were within a narrow range. According to several previous studies Dentomaxillofac Radiol, 45, 20160200 birpublications.org/dmfr DTI of the IAN using 3T MRI that evaluated DTI of the peripheral nerves, the FA of an injured nerve became significantly lower than that of the normal nerve.…”
Section: Discussionsupporting
confidence: 69%
“…Manoliu et al 18 initially reported the quantitative evaluation of the IAN using DTI data in a small number of healthy volunteers. Our study showed that FA values of the IANs ranged from 0.37 to 0.49, which were similar to the results in their study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Naturally, the aforementioned gain in SNR could have been invested in increasing other parameters, which might be favourable when evaluating other anatomical regions of the dentomaxillofacial region. 38 In particular, decreasing the spatial resolution (i.e. decreasing the matrix size while keeping the field of view constant) and/or increasing the number of signal SD, standard deviation.…”
Section: High-permittivity Dielectric Padsmentioning
confidence: 99%